2012
DOI: 10.1007/978-3-642-31454-4_23
|View full text |Cite
|
Sign up to set email alerts
|

Towards Adaptive Information Visualization: On the Influence of User Characteristics

Abstract: Abstract. The long-term goal of our research is to design information visualization systems that adapt to the specific needs, characteristics, and context of each individual viewer. In order to successfully perform such adaptation, it is crucial to first identify characteristics that influence an individual user's effectiveness, efficiency, and satisfaction with a particular information visualization type. In this paper, we present a study that focuses on investigating the impact of four user characteristics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
86
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 24 publications
19
86
0
1
Order By: Relevance
“…This result, however, is consistent with findings in [28], which showed that bar and radar graph expertise may only have significant effects on user visualization preference, but not on performance. These findings suggest that there might not be easily detectable differences in the visualization processing behaviors of experts and novices, as defined by our self-rated measures of expertise.…”
Section: Bar and Radar Graph Expertisesupporting
confidence: 92%
See 4 more Smart Citations
“…This result, however, is consistent with findings in [28], which showed that bar and radar graph expertise may only have significant effects on user visualization preference, but not on performance. These findings suggest that there might not be easily detectable differences in the visualization processing behaviors of experts and novices, as defined by our self-rated measures of expertise.…”
Section: Bar and Radar Graph Expertisesupporting
confidence: 92%
“…This finding provides encouraging evidence that this cognitive ability could be reliably detected in real time using gaze information. This result is particularly important for our long-term goal of designing user-adaptive visualizations, especially in light of previous studies, which showed that low perceptual speed can negatively affect task performance, in terms of both accuracy [3] as well as task completion time [28]. We have shown that perceptual speed influences AOI-specific gaze measures relating to the Legend, Labels and High AOIs.…”
Section: Summary Of Findings and Discussionmentioning
confidence: 71%
See 3 more Smart Citations